2011
DOI: 10.1111/j.1582-4934.2010.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cells and metastatic colorectal cancer cells shared the common endogenous human microRNA-26b

Abstract: The increase in proliferation and the lack of differentiation of cancer cells resemble what occur in the embryonic stem cells during physiological process of embryogenesis. There are also striking similarities in the behaviour between the invasive placental cells and invasive cancer cells. In the present study, microarrays were used to analyse the global expression of microRNAs in a human embryonic stem cell line (i.e. HUES-17) and four colorectal cancer (CRC) cell lines (i.e. LoVo, SW480, HT29 and Caco-2) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 58 publications
(76 reference statements)
11
41
0
Order By: Relevance
“…As reported in our previous studies of a potential oncofoetal CRC biomarker, certain high-value biomarkers, including miRNAs, genes and cancer proteins, show embryonic characteristics [10][11][12][13] . Tumorigenesis and embryogenesis have been postulated to share certain common pathways 10 .…”
supporting
confidence: 61%
“…As reported in our previous studies of a potential oncofoetal CRC biomarker, certain high-value biomarkers, including miRNAs, genes and cancer proteins, show embryonic characteristics [10][11][12][13] . Tumorigenesis and embryogenesis have been postulated to share certain common pathways 10 .…”
supporting
confidence: 61%
“…7,48,49 The diminished expression of miR-26b, as seen in the HCV-positive lymphoma group, has been linked to a malignant tumor phenotype in hepatocellular carcinoma 50 and lung carcinoma 51 as well as in cell culture models of colon cancer and diffuse large B-cell lymphoma. 52,53 Moreover, overexpression of miR-26b in colon cancer cell lines led to significant suppression of cell growth and the induction of apoptosis. 53 Epidemiological data clearly link HCV infection with a higher risk of lymphoma development.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Moreover, overexpression of miR-26b in colon cancer cell lines led to significant suppression of cell growth and the induction of apoptosis. 53 Epidemiological data clearly link HCV infection with a higher risk of lymphoma development. 54,55 Moreover, eradication of the virus by antiviral therapy can lead to lymphoma remission, which points to a causal role of HCV in malignant transformation, as reviewed by Arcaini et al 15 SMZL is one of the subentities of B-cell nonHodgkin lymphoma found associated with HCV infection in a statistically significant manner.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, large-scale analysis revealed a miR-26 target site in the Ctdsp2 39 UTR that is bound by a miRNA silencing complex in the mouse brain (Chi et al 2009). Finally, the regulated feedback by miR-26a and miR-26b might be important not only in neurons, but for proliferation/differentiation events in general, as both family members have been implicated with differentiation of other cell types, stemness, and cancer (Wong and Tellam 2008;Huse et al 2009;Kota et al 2009;Ma et al 2010). …”
Section: Right Panel)mentioning
confidence: 99%